On j-conjugate product of quaternion polynomial matrices - Wu, Ai-Guo; Liu, Wanquan; Li, Caheng; Duan, Guang-Ren (Elsevier, 2013)
In this paper, the concept of j-conjugate product over quaternion polynomial matrices is proposed. Further, some interesting properties of the proposed j-conjugate products are derived. By means of j-conjugate product, necessary and sufficient conditions for consimilarity over quaternion matrices are finally established.